Images of English Writers in the Novel «Old England» by E. L. Lann - Zhatkin, Dmitry Nikolayevich; Mushkova, Victoria V. (Journal of History Culture and Art Research, 2018)
Objectives: The article is aimed at understanding the peculiarities of the Soviet historical novel «Old England» by E.L. Lann, in particular, the unique images of the famous English writers Jonathan Swift, Joseph Addison and Alexander Pope. Methods: The article is methodologically based on research in the field of textology and poetics of the historical novel, of problems of intercultural communication, dialogue and «someone else’s word», and semiotics. In the process of analysis, cultural-historical, comparative-historical, historical-typological, historical-genetic approaches, as well as methods of problematic, comparative analysis of artistic works were used. Findings: The novel by E.L. Lann «Old England» recreates the social, cultural and literary life of England in the first half of the 18th century, in the time of opposition between Whigs and Tories, and contains vivid portraits of leading writers. In the foreground there is the figure of Jonathan Swift, who was worried about the fate of literature because it was losing the educative value and stopping to guide readers to higher ideals, accentuating the inferior principles of being. E.L. Lann shows the political parties in power, or aspiring to it, using the talents of many writers in their own interests due to the venality of the latter. Novelty: «Old England» is written in the traditions of the Soviet novel, but it has a number of features, that was stipulated by the unusual nature of the characters and by the special way of discovering characteristics of heroes.